Flavonoids in Cancer Metastasis - Liskova, Alena; Koklesova, Lenka; Samec, Marek; Smejkal, Karel; Samuel, Samson Mathews; Varghese, Elizabeth; Abotaleb, Mariam; Biringer, Kamil; Kudela, Erik; Danko, Jan; Shakibaei, Mehdi; Kwon, Taeg Kyu; et al. (Cancers, 2020)
Metastasis represents a serious complication in the treatment of cancer. Flavonoids are plant secondary metabolites exerting various health beneficiary effects. The effects of flavonoids against cancer are associated not only with early stages of the cancer process, but also with cancer progression and spread into distant sites. Flavonoids showed potent anti-cancer effects against various cancer models in vitro and in vivo, mediated via regulation of key signaling pathways involved in the migration and invasion of cancer cells and metastatic progression, including key regulators of epithelial-mesenchymal transition or regulatory molecules such as MMPs, uPA/uPAR, TGF-β and other contributors of the complex process of metastatic spread. Moreover, flavonoids modulated also the expression of genes associated with the progression of cancer and improved inflammatory status, a part of the complex process involved in the development of metastasis. Flavonoids also documented clear potential to improve the anti-cancer effectiveness of conventional chemotherapeutic agents. Most importantly, flavonoids represent environmentally-friendly and cost-effective substances; moreover, a wide spectrum of different flavonoids demonstrated safety and minimal side effects during long-termed administration. In addition, the bioavailability of flavonoids can be improved by their conjugation with metal ions or structural modifications by radiation. In conclusion, anti-cancer effects of flavonoids, targeting all phases of carcinogenesis including metastatic progression, should be implemented into clinical cancer research in order to strengthen their potential use in the future targeted prevention and therapy of cancer in high-risk individuals or patients with aggressive cancer disease with metastatic potential.